Halal Food in Muslim Minority Tourism Destinations: Perspective of Toraja, Indonesia - Takdir Takdir; Ambas Hamida (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Despite growing scholarly interest in halal tourism, there is still a gap on the study on the availability of halal food in areas where Muslims are not the dominant demographic. This has become an unresolved problem in the Indonesian tourism sector. Therefore, this current research examined the availability of halal food and the potential for developing halal cuisine in Tana Toraja,Indonesia. Data were collected through observation, interviews, and documentation from four informants consisting of the Tourism officers, the Indonesian Ulema Council, food sellers, and visitors. The data were analyzed through a process of data reduction, data presentation, and conclusion drawing. The findings revealed that Toraja, as a Muslim minority region, has limited access to halal food. Furthermore, the research identified a significant opportunity and potential for halal cuisine development through collaboration among stakeholders. Consequently, it is imperative that the government and tourism managers prioritize the availability of halal food in Tana Toraja.